COI mtDNA barcoding and morphology for species delimitation in the spider genus Ixchela Huber (Araneae: Pholcidae), with the description of two new species from Mexico - Valdez-Mondragón, Alejandro (Zootaxa, 2020)
The spider genus Ixchela Huber 2000, is comprised of 22 species distributed from north-eastern Mexico to Central America, including the two new species described herein from Mexico: Ixchela panchovillai sp. nov. and Ixchela zapatai sp. nov., both from the state of Oaxaca and described for both sexes. DNA barcoding utilizing mitochondrial cytochrome c oxidase subunit 1 (COI) and morphology were used for species delimitation. Molecular analyses and species delimitation included four methods: 1) corrected p-distances under neighbor-joining (NJ), 2) general mixed yule coalescent model (GMYC), 3) automatic barcode gap discovery (ABGD), and 4) Poisson tree processes (bPTP). All molecular methods and morphology were consistent in delimiting and recognizing the two new species describing herein. The average inter-specific genetic distance (p-distance) within the genus Ixchela is 12%. Ixchela panchovillai sp. nov. is closely related in the NJ analysis with I. placida, with an average p-distance of 7.9%, whereas I. zapatai sp. nov. is closely related to I. taxco, with an average p-distance of 8.4% between both species. Additionally, identification keys for males and females of the genus Ixchela are presented.